Cost Minimization Analysis of Hypnotic Drug: Target Controlled Inhalation Anesthesia (TCIA) Sevoflurane and Target Controlled Infusion (TCI) Propofol - Wiryana, Made; Aribawa, I Gusti Ngurah Mahaalit; Senapathi, Tjokorda Gde Agung; Widnyana, I Made Gede; Hartawan, I Gusti Agung Gede Utara; Sucandra, Made Agus Kresna; Parami, Pontisomaya; Putra, Kadek Agus Heryana; Sutawan, IB Krisna Jaya; Arimbawa, IGNA Putra; Jaya, Ketut Semara; Semarawima, Gede (BALI MEDICAL JOURNAL, 2016)
Background: Cost minimization analysis is a pharmaco-economic study used to compare two or more health interventions that have been shown to have the same effect, similar or equivalent. With limited health insurance budget from the Indonesian National Social Security System implementation in 2015, the quality control and the drug cost are two important things that need to be focused. The application of pharmaco-economic study results in the selection and use of drugs more effectively and efficiently. Objective: To determine cost minimization analysis of hypnotic drug between a target controlled inhalation anesthesia (TCIA) sevoflurane and a target controlled infusion (TCI) propofol in patients underwent a major oncologic surgery in Sanglah General Hospital. Methods: Sixty ASA physical status I-II patients underwent major oncologic surgery were divided into two groups. Group A was using TCIA sevoflurane and group B using TCI propofol. Bispectral index monitor (BIS index) was used to evaluate the depth of anesthesia. The statistical tests used are the Shapiro-Wilk test, Lavene test, Mann- Whitney U test and unpaired t-test (? = 0.05). The data analysis used the Statistical Package for Social Sciences (SPSS) for Windows. Results: In this study, the rate of drug used per unit time in group A was 0.12 ml sevoflurane per minute (± 0.03) and the group B was 7.25 mg propofol per minute (±0.98). Total cost of hypnotic drug in group A was IDR598.43 (IQR 112.47) per minute, in group B was IDR703.27 (IQR 156.73) per minute (p>0.05). Conclusions: There was no statistically significant difference from the analysis of the drug cost minimization hypnotic drug in a major oncologic surgery using TCIA sevoflurane and TCI propofol.